STRATEGI PENGEMBANGAN BUMDES UNTUK MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT DESA - Aninda Megasari; Siswandari Siswandari; Nurhasan Hamidi (Universitas Sebelas Maret, 2022)
ABSTRACT The purpose of the study is to find out the existence of 1) the development strategy of BUMDes in Karanganyar to improve the economic welfare of the people of Village; 2) inhibiting factors and supporting factors for the development strategy of BUMDes to improve the economic welfare of the people of Village; 3) the solution of factors inhibiting the development strategy of BUMDes. This research is a descriptive qualitative research. The data sources used in this study are primary data sources and secondary data sources with a total of 8 informants. Data collection techniques using observation, interview, and documentation methods. The data analysis techniques used in this study are data collection, data reduction, data presentation, and drawing conclusions. The data validity test in this study used source triangulation, engineering triangulation, and time triangulation. The results of the research conducted showed: 1) there are three processes of the BUMDes development strategy in improving the economic welfare of the people of Village, namely the first process of strategy formulation, the process of implementing strategies, and the process of evaluating strategies. 2) there are inhibiting factors and supporting factors in the BUMDes development strategy to improve the economic welfare of the people of Village 3) there is a solution to the inhibiting factors in the development strategy of BUMdes to improve the economic welfare of Village. Keywords: Economic welfare, development strategies, BUMDes ABSTRAK Tujuan dari penelitian adalah untuk mengetahui adanya 1) strategi pengembangan BUMDes di Karanganyar untuk meningkatkan kesejahteraan ekonomi masyarakat ; 2) faktor penghambat dan faktor pendukung strategi pengembangan BUMDes untuk meningkatkan kesejahteraan ekonomi masyarakat Desa; 3) solusi faktor penghambat strategi pengembangan BUMDes. Penelitian ini merupakan penelitian kualitatif deskriptif. Adapun sumber data yang digunakan dalam penelitian ini adalah sumber data primer dan sumber data sekunder dengan jumlah informan sebanyak 8 orang. Teknik pengumpulan data dengan menggunakan metode observasi, wawancara, dan dokumentasi. Teknik analisis data yang digunakan dalam penelitian ini yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Uji validitas data pada penelitian ini menggunakan triangulasi sumber, triangulasi teknik, dan triangulasi waktu. Hasil penelitian yang dilakukan menunjukan: 1) terdapat tiga proses strategi pengembangan BUMDes dalam meningkatkan kesejahteraan ekonomi masyarakat Desa yaitu proses yang pertama proses perumusan strategi, proses penerapan strategi, dan proses pengevaluasian strategi. 2) terdapat faktor penghambat dan faktor pendukung dalam strategi pengembangan BUMDes untuk meningkatkan kesejahateraan ekonomi masyarakat Desa 3) adanya solusi pada faktor penghambat dalam strategi pengembangan BUMdes untuk meningkatkan kesejahteraan ekonomi Desa. Kata kunci: Kesejahteraan ekonomi, strategi pengembangan, bumdes